Performance Evaluation and Optimum Portfolio Allocation for Stocks of Agribusiness and Non-Agribusiness Companies in ILQ45 - Azizatun Nurhayati; Any Suryantini; Jamhari Jamhari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
Investors need fundamental aspects to allocate their fund in a set of efficient portfolio to maximize their yield. One of many fundamental aspecs is risk and return stocks price analysis. There were some agribusniness companies and non-agribusiness companies listed in ILQ45. This study was aimed to know stock performance of agribusiness companies compared with non-agribusiness companies which were listed in Index Liquid 45 in Indonesia Stock Exchange and to allocate optimum portfolio with cut off point method and randomly designed methode. Data of monthly from August 2011-December 2015 was used in this study. The result showed that range of return of agribusiness companies was -13.24% up to 20.098% and non-agribusiness was 49.50% up to 10.39%. Range of standard deviation for agribusiness companies was 6.43%-14.36% and 5.87-15.54% for non-agribusiness. Range of positive coefficient of variance (CV) for agribusiness was 3.59-18.61 and 5.47-59.19. Optimum portfolio formed by Unilever Indonesia (61.27%), Indofood ICBP (32.27%), BCA (3.81%), and BRI (2.65%). Return of optimum portfolio was 21.77% year on year and it was the highest return among portofolios which were formed randomly.